Legal Perspectives on the South China Sea Dispute - Muhammad Syamsuddin; Mira Nila Kusuma Dewi; Andy Kurnia Anwar; Muh. Arie; Zeth Nathaniel Patadungan; Riswan Evandri (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Legal issues at the international level are more complex and complicated compared to conflicts within a specific territorial jurisdiction. This is because international legal matters may involve multiple countries simultaneously and require significant efforts for resolution. The case discussed in this paper concerns the South China Sea dispute, brought by the Philippines as one of the countries claiming rights over the South China Sea. The Philippines submitted the dispute with China to the International Arbitration forum. The Philippines argued that China’s actions in constructing artificial islands have caused severe damage to coral reef environments. Further analysis of this case will be discussed in more detail in the sections below.